L’Habitat inhabitable : le sous‑terrain comme lieu de vie - Marie Trossat (Ambiances)
Based on a research on the habitability of underground space, this article initiates a discussion on the concept of the “uninhabitable habitat”. If underground space is fundamentally uninhabitable and cannot be programmed as an habitat even in so-called temporary forms, our analysis questions the thresholds of acceptability. By describing three inhabited underground spaces – the shelters of the Civil Protection in Geneva in 1999 and from 2004 to 2018, the underground of the Gare du Nord in Brussels from 2016 to 2019 and the heating tunnels in Bucharest from 1990 to 2015 – the article sheds light on the living conditions of these spaces with regard to the status of their occupants, the genealogy of their occupations, their management modalities and the resulting ambiances. The uninhabitable character of the underground space is constituted around its own ambiances and symbolism: it calls upon themes such as atrophy, illness, prison, (in)visibility, dissuasion, violence or death. In this sense, the unbreathable character of underground space is not only qualified in its materiality, but also in the injunctions that guide it and in the place it provides or deprives. Finally, the concept of uninhabitable habitat aims at exploring the extraordinarily common of our built environment and to establish levers for action in the situations of undesirability that it implies.